Diet composition and feeding habits of Acetes japonicus (Decapoda: Sergestidae) in estuarine waters of Tanjung Dawai, Kedah, Malaysia - Alsayed, Amani Abdulaziz A. (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
This study describes the diet composition and feeding habits of sergestid shrimps Acetes japonicas. The stomach contents of 330 specimens, captured from the Estuary of Tanjung Dawai, Kedah from June 2008 - May 2009 were analysed. Analysis on the percentage of numerical abundance (Ci) showed that plant matter (28.18%) and crustacean appendages (18.70%) as the two highest values amongst the eight categories of feeding items. In addition, percentage frequency of occurrence (Fpi) values of phytoplankton, zooplankton, algae, plant matter, appendages of crustacean, debris, unidentified items and sand-mud were 3.54%, 7.05%, 5.07%, 27.44%, 17.42%, 15.80%, 8.94% and 19.81% respectively. Based on the food composition found in the stomach, it could be concluded that A. japonicus is a bottom feeder omnivorous.